2021
DOI: 10.3390/ijerph18147247
|View full text |Cite
|
Sign up to set email alerts
|

Can Watching Online Videos Be Addictive? A Qualitative Exploration of Online Video Watching among Chinese Young Adults

Abstract: Watching online videos (including short-form videos) has become the most popular leisure activity in China. However, a few studies have reported the potential negative effects of online video watching behaviors (including the potential for ‘addiction’) among a minority of individuals. The present study investigated online video watching behaviors, motivational factors for watching online videos, and potentially addictive indicators of watching online videos. Semi-structured interviews were conducted among 20 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…Moreover, some of them used SVAs all day long and put SVAs use ahead of other daily routines, even if they had experienced undesirable health consequences [ 10 , 11 ]. An increasing number of studies have shown that problematic smartphone use may cause a range of physical and psychological problems, including low-quality sleep, body aches, dry and blurry eyes, anxiety, depression, decreased face-to-face interactions, and social isolation [ 12 , 13 , 14 , 15 ]. To prevent middle-aged users from suffering the health hazards associated with the problematic use of SVAs, the current study tries to explicate the mechanism of problematic SVAs use among middle-aged Chinese adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some of them used SVAs all day long and put SVAs use ahead of other daily routines, even if they had experienced undesirable health consequences [ 10 , 11 ]. An increasing number of studies have shown that problematic smartphone use may cause a range of physical and psychological problems, including low-quality sleep, body aches, dry and blurry eyes, anxiety, depression, decreased face-to-face interactions, and social isolation [ 12 , 13 , 14 , 15 ]. To prevent middle-aged users from suffering the health hazards associated with the problematic use of SVAs, the current study tries to explicate the mechanism of problematic SVAs use among middle-aged Chinese adults.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the problematic use of the internet and smartphones, problematic SVAs use is a relatively new phenomenon that has received limited scholarly attention [ 7 , 14 ]. Notably, researchers have often used the terms excessive use, problematic use, and addiction interchangeably in internet and smartphone studies [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…UGC on the internet is not merely used for entertainment or passing time but may also weakens the boredom of daily life ( Poon and Leung, 2013 ). However, scholars also pointed out that the richness of short video contents has intensified individuals’ addiction to short videos to some extent ( Yang et al, 2021 ), thereby reducing individuals’ interest in the surrounding things in daily life. Nowadays, many individuals choose to use mobile phones for temporary entertainment after work or study to reduce fatigue and boredom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The high number of adolescent social media users has a positive impact on adolescents in the form of developing the capability to socialize, communicate, and friendships to cross countries, opening opportunities for learning through simplicity to access the information [1]- [3]. Contradictorily, this media is also could be able to provide unlimited access to impressions that smell of violence [4], pornography [4], [5], triggering cyberbullying [6], [7] and social media addiction [8], [9]. As the explanation of the theory of uses and gratification in the theory of communication, it is explained that each individual has a certain purpose based on his requirements by using media that are considered appropriate [10], [11].…”
Section: Introductionmentioning
confidence: 99%